PERAN GURU PENDIDIKAN PANCASILA DALAM MENUMBUHKAN SIKAP BELA NEGARA SISWA DI SMP NEGERI 14 SEMARANG - Sumiati, Sumiati; Suneki, Sri; Maryanto, Maryanto (Civis : Jurnal Ilmiah Ilmu Sosial dan Pendidikan, 2024)
The background of this research is the lack of students’ national defense attitude at SMP Negeri 14 Semarang, this show that there are still students who have not participated in the ceremony solemnly, a small number of students throw rubbish carelessly, do not wear complete attributes, and pay less attention to the teacher when teaching. This purpose of this research is to describe the role of Pancasila Education subject teachers in fostering students’ national defense attitudes at state Junior High School 14 Semarang. The research method used is a qualitative approach with descriptive methods. Data collection techniques were obtained through interviews, observation and documentation. Test the validity of the data in this research using triangulation of data sources. The data analysis techniques in this research are data collection, drawing conclusions and data validation. The research results show that : 1) the implementation of a national defense attitude in learning is carried out through preliminary activities, core activities and closing activities. 2) efforts to foster an attitude of defending the country through learning are carried out through habituation activities, role models and contextual examples. 3) efforts to foster an attitude of defending the country through extracurricular activities are carried out through flag ceremonies, material provision, motivation and example. 4) efforts to foster an attitude of defending the country through habituation activities can be carried out through exemplary and habituation activities.